Betwixt, between, or beyond? : Negotiating 'Trans' formations from the Liminal Sphere of Contemporary Black Performance Poetry. - Bauridl, Birgit M. (American Studies - A Monograph Series - Band 215., 2013)
Hauptbeschreibung 'Betwixt, between, or beyond?' is the first study of contemporary black performance poetry from the viewpoint of transnational American Studies. It investigates a vast array of performances ranging from online recordings to political rallies to the poetry slam and Broadway stage. Black poets discussed come from diverse personal and cultural backgrounds and include, e.g., Patricia Smith, Staceyann Chin, Taalam Acey, Bryonn Bain, and Tshaka Campbell. Developing an approach rooted in anthropological, ethnographic, and theatrical perceptions of performance, the study e.